APRESIASI MASYARAKAT TERHADAP TRADISI LISAN PERMAINAN RAKYAT JARAN KEPANG DI KANAGARIAN SIMALIDU KECAMATAN KOTO SALAK KABUPATEN DHARMASRAYA - Nani Kurniasih; Nurizzati Nurizzati; Zulfikarni Zulfikarni (Faculty of Languages and Arts, Universitas Negeri Padang, 2012)
The perposes of this researeh are to describe and the explain the appreciation of society in kanagarian Simalidu Kecamatan Koto Salak Kabupaten Dharmasraya. West Sumatra to the Jaran Kepang. The research is using the descriptive methade and the of this research is qualitative the issues that describe is type the appreciation and the acceptance of the society to Jaran Kepang in Kanagarian Simalidu Kecamatan Koto Salak Kabupaten Dharmasraya. That obtainable through the questionnaire and interview that using by the instrument in this research. The accumulation technique of data that using here are: (1) the observation to searching the informan that requires in the research, (2) give the questionnaire that contain same questions that have to be answered by the society in Kanagarian Simalidu Kecamatan Koto Salak Kabupaten Dharmasraya, (3) The structural interview, by using some questions to the informans based an the research, (4) record, by recorded oral data that express by the informans, (5) note, by kating all the informan that has bean obtained from the observation the interview, and the recard.